Çamaşır Makinalarının Akıllı Kontrolu İçin Gerekli Parametre Ve Değişkenlerin İncelenmesi - Dinçmen, Erkin (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada, çamaşır makinası için bir akıllı kontrol uygulamasında giriş olarak kullanılabilecek parametrelerden su sertliğinin, çamaşır miktarının, çamaşır cinsinin, kir ve deterjan miktarının algılanması üzerinde durulmuştur. Bu amaçla önce teorik bir çalışma yapılarak çeşitli ölçme yöntemleri araştırılmış, daha sonra parametrelerin ölçülebilirliğinin incelenmesi amacıyla deneysel çalışmalar yapılmıştır. Yük miktarı algılama deneyleri çamaşırların su emme miktarlarının gözlemlenmesi, yük cinsi algılama deneyleri ise çamaşırların su emme, su salma kabiliyetlerinin gözlemlenmesine dayanarak gerçekleştirilmiştir. Daha sonra kir ve deterjan algılama deneylerine geçilmiştir. Bu çalışmalar iki aşamada gerçekleştirilmiştir. Birinci aşamada çamaşır makinasından bağımsız olarak beherlerde hazırlanan çeşitli çözeltiler ile çalışılmış ve bir bulanıklık-iletkenlik sensörüyle kir ve deterjan algılamanın gerçekleştirilip gerçekleştirilemeyeceğine bakılmıştır. İkinci aşamada ise çamaşır makinasında deneyler yapılmış, kir algılama daha ileriki bir çalışma konusu olarak düşünülüp deterjan algılama üzerinde yoğunlaşılmıştır. Çalışmanın sonunda ise teorik ve deneysel çalışmalardan elde edilen bilgi birikimi kullanılarak çamaşır makinası için bir akıllı kontrol yapısı önerilmiştir.

In this study, research has been done for detecting various parameters such as water hardness, amount of clothes, type of clothes, degree of dirtiness of clothes and amount of detergent, which can respectively be used as input parameters of an intelligent control of a washing machine. During research, a theorical study and investigation has been held on different measurement techniques, culminating the experimental procedure that has been performed in order to identify the measurability of the said parameters. The experimental studies for detecting the cloth amount were based on examining the amount of water absorbed by the clothes while the studies for detecting the cloth types were based on the water absorption and desorption capabilities of the clothes. Research for detecting the dirt and detergent has been done in two steps. The first step comprises experiments which have been performed on various chemical solutions prepared in laboratory flasks apart from the washing machine in order to observe whether it is possible to detect the dirt and detergent with a turbidity-conductivity sensor or not. In the second step, the experiments have been performed in the washing machines, focusing on detecting the amount of detergent, as dirt detection was considered to be the subject of a future research. And finally, culminating the experimental and theorical study an intelligent control structure for a washing machine has been designed and proposed.
An Investigation On The Necessary Parameters And Variables For Intelligent Control Of Washing Machines
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2003
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2003
Keywords: Çamaşır Makinası; Bulanıklık; İletkenlik; Çamaşır Miktarı; Çamaşır Cinsi; Kir Miktarı; Deterjan Miktarı; Su Sertliği; Akıllı Kontrol; Yapay Sinir Ağı; Bulanık Mantık.; Washing Machine; Turbidity; Conductivity; Amount of Clothes; Type of Clothes; Amount of Dirt; Amount of Detergent; Water Hardness; Intelligent Control; Artificial Neural Network; Fuzzy Logic.